ADRB2 Gln27Glu polymorphism influenced changes in leptin but not body composition or metabolic and other inflammatory parameters after twelve weeks of combined training in overweight adolescents - Neiva Leite; Larissa Rosa da Silva; Íncare Correa de Jesus; Wendell Arthur Lopes; Claudia Regina Cavaglieri; Cássio Leandro Consentino; Rosana Bento Radominski; Ricardo Lehtonen Rodrigues de Souza; Luciane Viater Tureck; Lupe Furtado-Alle (Universidade Estadual Paulista (UNESP), 2018)
ABSTRACT Aim To compare the anthropometric, metabolic, and inflammatory parameters of overweight adolescents after 12-weeks of resistance and aerobic training (CT), taking into account the Gln27Glu polymorphism of the β2 adrenergic receptor (ADRB2) gene. Methods Forty-seven adolescents (15.05±1.07y) were assigned to one of four groups, according to the presence or absence of the Glu27 allele: CT (CarrierT n=11; NoncarrierT n=11) or control (CarrierC n=13; NoncarrierC n=12). Body composition, abdominal fat, maturation, fitness, metabolic and lipid profile, inflammatory markers were assessed. The CT consisted of six resistance exercises, followed by 30 min of walking/running at 50-80% VO2max, totaling 60 min/session, three times a week. A mixed-model factorial ANOVA was used to compare variables at baseline and after 12-weeks. Results TC was effective in reducing total fat mass (NoncarrierT ES=.45, CarrierT ES=.27) and subcutaneous abdominal fat (NoncarrierT ES=.48, CarrierT ES=.46) and increasing lean mass (NoncarrierT ES=.58, CarrierT ES=.60) and fitness. CarrierT group showed a reduction in leptin (ES=.49). Conclusion The responses of body composition and physical fitness to TC were not influenced by the presence of the Gln27Glu polymorphism. However, only the Glu27 allele carriers showed reductions in leptin after 12-weeks. Besides, a lack of intervention caused obesogenic effects, especially in Glu27carriers.